Party-system fragmentation and its effect on likelihood of voting: the moderating role of polarization - Valentim, Vicente Dinis (2017)
The relation between party-system fragmentation and turnout is a puzzling one. Theoretically, some authors argue that higher fragmentation boosts turnout, whereas others argue the opposite. Empirically, different studies have paid support to both these expectations. This dissertation aims to shed some light over this controversy. It contends that these conflicting results are due to a neglect of the moderating role that polarization is expected to play over the relation between fragmentation and turnout. In highly polarized party systems, parties are likely to provide voter with more differentiated alternatives. Thus, a higher number of parties is likely to work as an incentive to voting, by increasing overall levels of party identification and increasing the likelihood that the mobilization efforts of parties will reach different voters. Yet in poorly polarized systems, as the higher number of parties does not translate into a richer array of options, increasing fragmentation should depress voter turnout, by making it harder to collect information on the parties and putting the same voter under cross pressures. These expectations are tested through a survey experiment. The results support the main argument. Fragmentation has a positive effect over likelihood of voting in highly polarized contexts, but a negative one in lowly polarized contexts. The negative effect of fragmentation over likelihood of voting when polarization is low is partly mediated by the cognitive costs of voting. In highly polarized contexts, it is rather the intensity of preference for a party that partly mediates the relation, although this mediation has a direction opposite to expected